Biomineralization of Dental Tissues Treated with Silver Diamine Fluoride. (September 2021) - Sulyanto, R.M.; Kang, M.; Srirangapatanam, S.; Berger, M.; Candamo, F.; Wang, Y.; Dickson, J.R.; Ng, M.W.; Ho, S.P.
Silver diamine fluoride (SDF) is a dental biomaterial used to arrest dental caries. To better understand SDF's mechanism of action, we examined the localization of silver within the tissues of SDF-treated teeth. Carious primary teeth fixed within 2 min of SDF application (SDF-minutes, n = 3), at 3 wk after SDF application in vivo (SDF-weeks, n = 4), and at 2 y after multiple SDF applications in vivo (SDF-multiple, n = 1) were investigated in this study. Carious primary teeth without SDF application (no-SDF, n = 3) served as controls. Mineral density and structural analyses were performed via micro–X-ray computed tomography and scanning electron microscopy. Elemental analyses were performed through X-ray fluorescence microprobe and energy-dispersive X-ray spectroscopic techniques. SDF-treated teeth revealed higher X-ray–attenuated surface and subsurface regions within carious lesions, and similar regions were not present in no-SDF teeth. Regions of higher mineral density correlated with regions of silver abundance in SDF-treated teeth. The SDF penetration depth was approximated to 0.5 ± 0.02 mm and 0.6 ± 0.05 mm (mean ± SD) for SDF-minutes and SDF-weeks specimens, respectively. A higher percentage of dentin tubular occlusion by silver or calcium phosphate particles was observed in primary teeth treated with SDF-weeks as compared with SDF-minutes. Elemental analysis also revealed zinc abundance in carious lesions and around the pulp chamber. SDF-weeks teeth had significantly increased tertiary dentin than SDF-minutes and no-SDF teeth. These results suggest that SDF treatment on primary teeth affected by caries promotes pathologic biomineralization by altering their physicochemical properties, occluding dentin tubules, and increasing tertiary dentin volume. These seemingly serendipitous effects collectively contribute to the cariostatic activity of SDF.